Who and where are specialist nurses in enterostomal therapy in Brazil? (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To characterize the educational and professional profile of the Brazilian enterostomal therapist nurses with a view to assessing the scope of the specialty in the present and to map the professional practice in the specialty. Method: It is an exploratory and descriptive study with a quantitative approach conducted during 2016, carried out with 548 nurses, graduates, specialized in the area of enterostomal therapy. Data were collected by questionnaires and organized in the software Microsoft Excel®, presented in absolute numbers and percent in the form of graphs and tables. Results: The data point to growth pathways of enterostomal therapy education programs, their dissemination in the country’s regions and expansion of the number of graduates, as well as the predominance of the Southeast region for the formation and performance of the enterostomal therapist nurses. As for the areas of professional practice, there is a greater concentration of professionals in the care of people with wounds and in the care area. Conclusion: Most Brazilian enterostomal therapists have been working in the area for less than 10 years, especially in the care area, predominantly in the care of people with injuries. One of the concerns pointed out by the study refers to the need for the specialist to act and disclose the other areas of the specialty – ostomy and incontinence.